69 Empirical ethics and palliative care: a systematic review of the ethical challenges identified by specialist palliative care practitioners in their day-to-day clinical practice. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Schofield, Guy; Dittborn, Mariana; Huxtable, Richard; Brangan, Emer; Selman, Lucy
Abstract : Background: Ethical issues arise daily in the delivery of palliative care. Despite much (largely theoretical) literature on the ethics of palliative care, evidence from specialist palliative care practitioners (SPCPs) about the day-to-day ethical challenges they encounter has not previously been synthesised. This evidence is crucial to inform education and training, and support staff. Aim: To synthesise the evidence regarding the ethical challenges which SPCPs of all professional backgrounds encounter during clinical practice. Methods: A prospectively registered systematic literature review using narrative synthesis methodology (Popay et al 2006) was conducted. Key words and subject headings of 8 databases (MEDLINE, Philosopher's Index, EMBASE, PsycINFO, LILACS, WHOLIS, Web of Science and CINAHL) were searched on 03/10/2018, without time limits. Eligible papers reported original research using inductive methods to describe SPCP-reported ethical challenges, in any language. Quality was dual assessed using the Mixed-Methods Appraisal Tool. Tabulation, textural description, concept mapping and thematic analysis were used to develop and present the narrative. Results: 7040 records were screened. 12 studies from 9 countries were included. All included studies examined adult care. A broad range of ethical challenges were identified in 5 themes: patient-related (e.g. autonomy, truth-telling), patient-family relationship (e.g. boundaries of confidentiality, family-patient conflict), clinical issues (e.g. futility, palliative sedation), organisational factors (e.g. value differences between professions and care settings, place of care), and wider system (e.g. euthanasia, organ donation). Conclusion: SPCPs encounter a broad range of ethical challenges, not all of which are recognised in the ethics literature or form part of training curricula. In particular, the challenges of differing value positions between hospice and curative sectors and genetics ethics seldom occur in theoretical discussions of palliative care ethics or training, while withdrawal of life-prolonging treatment and euthanasia are more commonly represented. Findings of the review can inform SPCP ethics education, training and support.